Detection of avian influenza virus in surface waters using passive samplers - Madison T. Gouthro; Emalie K. Hayes; Taylor Prest; Graham A. Gagnon (npj Viruses)
Abstract Avian influenza (AIV) remains a global concern not only for humans as a pandemic threat but pose a risk to poultry, wildlife, and livestock. The detection of AIV in the environment traditionally has relied on reactive surveillance, limiting proactive response. This study assessed the detection of Pan-influenza A virus (Pan-FluA) and hemagglutinin subtype H5 genes in surface water using novel passive samplers and molecular analyses. Pan-FluA RNA was detected at concentrations from 2.1 × 105 to 5.6 × 1012 copies sampler−1 and H5 RNA at concentrations from 2.2 × 104 to 1.8 × 1011 copies sampler−1. Detections aligned with fall migration and waterfowl activity but also underscored the importance of monitoring interface zones influenced by wildlife, agriculture, and wastewater. Among other hemagglutinin subtypes detected, sequence analyses confirmed the presence of H5 lineages consistent with those reported for H5N1, H5N6, and H5N8. These findings ultimately demonstrate the potential of surface water surveillance as a scalable strategy for AIV detection.